BOOK REVIEW : The Appearances of Memory. Mnemonic Practices of Architecture and Urban Form in Indonesia - Cuthbert, Alexander R. (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 1 No 1 (2014): April 2014DO - 10.24843/JRS.2014.v01.i01.p09, 2014)
-
Keywords: -